2000
DOI: 10.1074/jbc.m004914200
|View full text |Cite
|
Sign up to set email alerts
|

A Domain with Homology to Neuronal Calcium Sensors Is Required for Calcium-dependent Activation of Diacylglycerol Kinase α

Abstract: Hydrolysis of phosphatidylinositol 4,5-bisphosphate is a common mechanism of stimulus transduction (1). Diacylglycerol (DAG) 1 released in this reaction activates protein kinase C (PKC) and is then rapidly metabolized back to phosphatidylinositol in a series of reactions initiated by a diacylglycerol kinase (DGK). As such, DGKs attenuate DAG-mediated PKC activation (2). Recent studies indicate that DGKs are also activated by mechanisms independent of phosphoinositide turnover (3, 4). Diacylglycerol kinases cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
74
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 45 publications
12
74
1
Order By: Relevance
“…We confirmed that DGK␥-G494D possessed no detectable DGK catalytic activity in vitro (data not shown). The deletion of the N-terminal 259 residues, acting as an autoinhibitory site of type I DGK (22,37), resulted in only a 2-fold increase in DGK activity when assayed in vitro (data not shown). However, this mutant showed constitutive localization at the cell periphery ( Fig.…”
Section: D)mentioning
confidence: 99%
“…We confirmed that DGK␥-G494D possessed no detectable DGK catalytic activity in vitro (data not shown). The deletion of the N-terminal 259 residues, acting as an autoinhibitory site of type I DGK (22,37), resulted in only a 2-fold increase in DGK activity when assayed in vitro (data not shown). However, this mutant showed constitutive localization at the cell periphery ( Fig.…”
Section: D)mentioning
confidence: 99%
“…Regarding the specific activity, values of 3-20 pmol PA min Ϫ1 g of protein Ϫ1 were previously reported in biochemical studies for wheat (37) and tomato (17) DGK isoforms, both being significantly higher than the specific activity observed here for Arabidopsis AtDGK2. A specific activity of 0.4 pmol of PA min Ϫ1 g of protein Ϫ1 has been reported for the human DGK isoform (38), whereas another human DGK isoform, DGK␣, showed values higher than 20 pmol of PA min Ϫ1 g of protein Ϫ1 (39).…”
Section: Fig 2 Phylogenetic Analysis Of Plant Dgk Isozymesmentioning
confidence: 99%
“…A similar, previously unrecognized, aggregation of basic amino acids is present in the amino-terminal part of AtDGK1 ( 45 YTAFQWRRNINLSWTK-AIARSKKNPKARHKVP 76 ). The two monocot DGKs also contain basic amino acid segments, which are almost identical in sequence, upstream of DAG/PE-binding domain 1 (rice, 39 YT-VNQLNKNISLSLMKAIRARARKYKKLKDKVP 71 ; maize, n Y-TVNQLNKNISLSLIRAIKARAKRYKKSKDKVP nϩ32 , exact position not known, because of a missing 5Ј part in the assembled cDNA). In all four plant enzymes analyzed here, the distances between the upstream basic region and the first copy of the DAG/PE-binding domain (3 amino acids) and between the two copies of the DAG/PE-binding domains (12 amino acid residues), respectively, were strongly conserved.…”
Section: Atdgk2 and Related Plant Dgk Isozymes Contain A Unique Aggrementioning
confidence: 99%
“…T cells from DGK␣-deficient mice have enhanced responses (19), further confirming the relevance of this enzyme in regulating immune function. Structural-functional analyses showed that the regulatory N-terminal domain of the enzyme, containing a recoverin-like domain and a tandem of EF hand motifs, acts as a negative regulator of enzyme activation and receptor-induced membrane translocation (8,20). Translocation of wild type (wt) DGK␣ is a very rapid and transient event, whereas a catalytically inactive mutant form remains at the membrane for a longer period of time (18).…”
mentioning
confidence: 99%